If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(n+5)=12
We simplify the equation to the form, which is simple to understand
-3(n+5)=12
Reorder the terms in parentheses
+(-3n-15)=12
Remove unnecessary parentheses
-3n-15=+12
We move all terms containing n to the left and all other terms to the right.
-3n=+12+15
We simplify left and right side of the equation.
-3n=+27
We divide both sides of the equation by -3 to get n.
n=-9
| 2x^2+5/2x-3/2=0 | | =3x-4 | | -17+b/8=13 | | =4x+22 | | y^2-16=9 | | =4x+3 | | 1+1=# | | =2x+5 | | -9h-15=93 | | 2d+1=3d | | -3y+12=-48 | | 4r+4=5r | | 7+x=-x+9 | | 9s+3=57 | | S=-30+0.2y | | 3x^2+12x-6=0 | | 4x+8-5-3=360 | | 7(a-4)=160 | | x=14+2y | | 7(a-4)=169 | | 2x=4x+14 | | 6+(9*x)=-75 | | (X1+x2)/2 | | 4x+111=11x-8 | | -86-8x=9x-16 | | 4x+8=x+14 | | 1/7(14x+28)=2(x+2) | | 8x-28-x=400 | | 8x-28+x=400 | | 2(a+2b)-(a-3b)=0 | | 3x+6=-75 | | 8x-28-5x=400 |